2018
DOI: 10.1016/j.jasrep.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Mid-late Holocene environmental and cultural dynamics at the south-west tip of Europe (Doñana National Park, SW Iberia, Spain)

Abstract: A multi-proxy palaeoenvironmental study (pollen, non-pollen palynomorphs, charcoal particles, mollusk macrofauna) of coastal marshland in Doñana National Park (southwestern Iberian Peninsula) was undertaken to trace environmental change, human activities related to woodland clearance, and past land-use during the mid-late Holocene (~ 5000-2800 cal BP). The results of this study are combined with archaeological data from the Copper and Bronze Ages and are subsequently compared with those of similar research car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 99 publications
(171 reference statements)
1
15
1
2
Order By: Relevance
“…CHAR values at Viñuelas mire (Figure 3) are considerably low at the beginning of the record except for the small peak at the very bottom of the sequence. Low fire activity at Viñuelas during this period is somehow unexpected, considering the dominant dry conditions [83,84]. This behavior is marked in the Kruskal-Wallis test as different, and it is coherent with the other results ( Figure A3 in Appendix A).…”
Section: Climatic Influence: From 5000-3000 Cal Bpsupporting
confidence: 84%
“…CHAR values at Viñuelas mire (Figure 3) are considerably low at the beginning of the record except for the small peak at the very bottom of the sequence. Low fire activity at Viñuelas during this period is somehow unexpected, considering the dominant dry conditions [83,84]. This behavior is marked in the Kruskal-Wallis test as different, and it is coherent with the other results ( Figure A3 in Appendix A).…”
Section: Climatic Influence: From 5000-3000 Cal Bpsupporting
confidence: 84%
“…ka BP (García-Alix et al, 2013). Extensive deforestation related to mining activities was also detected in the closely located Doñana National Park (López-Sáez et al, 2018), which cannot be completely confirmed by our findings (Figure 3). At Lake Medina, the time around 3 cal.…”
Section: Mid To Late Holocene (Around 55-2 Cal Ka Bp)contrasting
confidence: 65%
“…In the eastern hemisphere the 4.2‐ka event caused disruption or deflection of the westerlies, the Indian Summer Monsoon and the East Asian Monsoon (Weiss, ). It led to an ~250‐year widespread drought in many mid‐ and low‐latitude regions that was broken perhaps only briefly, and has been linked to synchronous societal collapse, habitat‐tracking, and eventual resettlement and reorganization across Spain (López‐Sáez et al ., ), Greece (Davis, ), Egypt (Hassan et al ., ), Palestine (Harrison, ; Weiss, ), Mesopotamia (Weiss, ), the Indus Valley (Petrie et al ., ) and China (Li et al ., ).…”
Section: The New Holocene Subdivisionsmentioning
confidence: 99%